STRATEGIC COMMUNICATION AS A PHENOMENON IN PUBLIC SPEAKING - Якимчук, Віра (SWorldJournal, 2023)
In today’s hyper-connected world, effective public speaking is a crucial skill that extends beyond traditional arenas. It’s not limited to politicians, CEOs, or gifted speakers; it’s now indispensable for professionals, students, and everyone else. Howev